Multidisciplinary approach to treating complex immune dysregulation disorders: an adaptive model for institutional implementation - Henderson, Lauren A.; Abraham, Roshini S.; Ahmed, Aisha; Blount, Lindsey; Canna, Scott W.; Chaimowitz, Natalia S.; Chandrakasan, Shanmuganathan; Coates, Bria; Connelly, James A.; Cooper, Megan A.; Duncan, Christine N.; French, Anthony; et al. (Frontiers in Immunology, 2025)
Patients with immune dysregulation may present with varying combinations of autoimmunity, autoinflammation, immunodeficiency, atopy, lymphoproliferation, and/or malignancy, often with multisystem involvement. Recognizing specific patterns of immune dysregulation, coordinating and interpreting complex diagnostic testing, and choosing initial (often empiric) treatment can be challenging. Centers are increasingly assembling multidisciplinary teams (MDTs) to standardize evaluation and optimize treatment of patients with complex immune dysregulation (immune dysregulation MDTs [immMDTs]). However, published information on the composition and function of immMDTs is sparse, and there is little guidance for those seeking to establish or optimize an immMDT. To inform this review, we assembled a panel of 24 pediatric providers from multiple specialties who actively participate in immMDTs to provide expert opinion. We also conducted a search of the available information on pediatric immMDTs from PubMed. Based on these insights, we summarize the structure and function of active immMDTs across the United States and focus on best practices and context-dependent solutions that may enable institutions with varying goals, patient populations, and resources to establish an immMDT.